Avaliação de aterosclerose subcliníca e fatores de risco matabólicos em mulheres jovens com risco de doença cardiovascular - Claudia Maria Vilas Freire (2010)
Gestational diabetes is carbohydrate intolerance that begins or is first diagnosed in pregnancy and its prevalence rate varies between 2 and 7%. It is an opportunity to evaluate early stage of diabetes because these patients face 7.5 times higher risk of developing type 2 diabetes and the consequent increase in cardiovascular risk. Objective: To determine whether women with previous gestational diabetes (GDM) have signs of subclinical atherosclerosis and whether this would be an independent risk factor for this outcome. Methods: We evaluated 175 women between 18 and 47 years, non-smokers: 79 with previous GDM (pGDM), 30 with two or more cardiovascular risk factors (RFg) and 66 in the control group (CG). They underwent physical examination, automatic measurement of intima-media thickness (IMT) in segments of common carotid, internal and bifurcation bilaterally and laboratory evaluation. To validate the chosen method for assessment of subclinical atherosclerosis, the measurement of carotid IMT, a literature review of the technique, indications and interpretation of the examination was performed. The software used in this research for automated measuring the IMT was subsequently validated, with comparisons between automated and manual measurements and interobserver agreement by Bland-Altman. Clinical characteristics, prevalence of diabetes, hypertension (HT) and metabolic syndrome (MS), and the measures of the IMT of the groups were compared. It was rated the overall cardiovascular risk of the groups. Then, a univariate and multivariate linear regression with composed IMT as the dependent variable and age, study groups, blood glucose, waist, HDLc, total cholesterol, triglycerides, MS and HT as covariates. Results: This study demonstrated that automated measurement is faster, reproductible and had no systematic erros compared to manual measurement. The differences between measurements were not clinicaly important in most part of the time. Global cardiovascular risk of 94% of the patients was in the range of low risk. Previous GDM and RF groups showed, as expected, higher levels of blood pressure, blood glucose, total cholesterol, cLDL, triglycerides and lower levels of HDLc than the CG. Obesity and waist were more frequently observed in groups pGDM and RFg, and significantly higher in the RFg compared to pGDM. Mean IMT of almost all segments analyzed was higher in group pGDM compared with CG, except in the carotid bifurcation and right common carotid. The RFg only showed greater IMT than control in the composite measure, and less than the group pGDM the left carotid bifurcation. After univariate linear regression analyses, a multiple regression model was developed using composite IMT as the dependent variable and study groups, blood glucose, total cholesterol, cHDL, triglycerides, age, waist circumference and hypertension as covariates. In the final model, age, cholesterol and belonging to pGDM group were independently associated with IMT composite. This final model explains 36.6% of IMT variability by the variables included. Conclusion: previous GDM is associated with increased carotid IMT as an independent risk factor, along with total cholesterol and age. The increased IMT in this population of women, similar to those with two or more known cardiovascular risk factors, should encourage early primary care prevention in patients with pregnancy complicated by GDM.